Understanding erythroid physiology and pathology in humanized mice: A closer look - Lu, Lu; Liu, Chenfei; Chen, Lezong; Zhang, Xumiao; Su, Yinglin; Chou, Zhenzhen; Liang, Yang; Song, Yuanbin (British journal of haematology, 2025)
Summary Erythropoiesis, the process of red blood cell (RBC) development from haematopoietic stem cells, is crucial in haematology research due to its intricate regulation and implications in various pathologies such as anaemia and haemoglobinopathies. Humanized mice, created by introducing human cells or tissues into immunodeficient mice, offer a promising avenue in vivo approach. However, challenges persist in fully replicating human erythropoiesis in these models, particularly in generating mature human RBCs capable of sustained circulation. This review discusses the differences between human and mouse erythropoiesis, recent progress made using refined humanized mouse models for studying human erythropoiesis and erythropoietic disorders, the challenges that impede a faithful mimicking of human phenotypes in these mice and recommendations for future research improvements. Despite progress being made, enhancing the translational potential of humanized mouse models for human erythropoiesis research remains a priority. Erythropoiesis, the formation of red blood cells (RBCs) from haematopoietic stem cells (HSCs), is vital for understanding conditions like anaemia and haemoglobinopathies. However, studying this process in vivo is challenging due to the lack of accurate models. Traditional mouse models provide valuable insights but face limitations due to species‐specific differences that hinder the replication of human RBC development. Humanized mouse models, integrating human cells or tissues, offer a more realistic approach to studying human erythropoiesis. This review explores the differences between human and mouse erythropoiesis, highlights the achievements of humanized mouse models and addresses the challenges in replicating human erythroid biology. This discussion offers valuable insights for improving these models and advancing haematological research. Created in BioRender. https://www.biorender.com/.